Zur Auswahl von sozio-kulturellen Sachverhalten im DaF-Unterricht - KORZENIEWSKI, Jan (Uniwersytet im. Adama Mickiewicza, 1995)
The main subject of the author’s interest is the problem of including cultural contents and elements of the intercultural communication in teaching the German language to foreign students. Treating the process of learning a foreign language as learning a foreign cultural environment the author divides the knowledge of foreign culture into this of the explicit (among others encyclopaedic information) and implicit character (e.g. values, attitudes, beliefs).